2017
DOI: 10.1002/ps.4640
|View full text |Cite
|
Sign up to set email alerts
|

Association between ants (Hymenoptera: Formicidae) and the vine mealybug (Hemiptera: Pseudococcidae) in table‐grape vineyards in Eastern Spain

Abstract: Our results suggest that the ant species native to vineyards in eastern Spain induce population increases of the vine mealybug. Moreover, the provisioning of sugars can be a valuable tool for ant management and mealybug control. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
(122 reference statements)
1
22
1
Order By: Relevance
“…The latter method may allow the positive effects of ant presence (see [12]). Nevertheless, other studies have found that the presence of ants in citrus and vine groves was weakly related or not related at all to the presence of sap feeders [21,65]. In addition, some natural predators of aphids and coccids may even increase under ant presence in vineyards [51].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…The latter method may allow the positive effects of ant presence (see [12]). Nevertheless, other studies have found that the presence of ants in citrus and vine groves was weakly related or not related at all to the presence of sap feeders [21,65]. In addition, some natural predators of aphids and coccids may even increase under ant presence in vineyards [51].…”
Section: Introductionmentioning
confidence: 92%
“…Some plants produce nectars, other food rewards or offer shelter to ants in exchange for protection against herbivory, competing plants or even pathogens [13][14][15][16][17]. These rewards may also be aimed at distracting ants from tending sap feeders [18][19][20][21]. Several cases of these ant-plant mutualisms are mediated by extrafloral nectaries (EFNs), which have been described for 4017 plant species of over 450 evolutionary lineages (21% of vascular plant families), and are expected to be found in about 8000 species [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most successful biological control programs rely primarily on encrytid parasitoids [30], such as Anagyrus pseudococci (Girault), a parasitoid of P. ficus and other related mealybugs [26,29,[31][32][33]. Even in organic vineyards, natural enemies may not provide complete control-ants have been shown to disrupt mealybug biological control in vineyards [33][34][35][36] and P. ficus can find refuge from some natural enemy species under the vines bark [37]. Some mealybug species can also overwinter on the roots of grapevines, and rootstocks with resistance to mealybug would be a valuable tool as part of IPM.…”
Section: Introductionmentioning
confidence: 99%